Status and Conservation of Hangul (cervus Elaphus Hanglu) in its Relic Range Areas Outside Dachigam National Park, Kashmir - Ahmad, Khursheed; Qureshi, Qamar; Nigam, Parag; Suhail, Intesar (Indian Forester, 2013)
The present paper reports population of Kashmir red deer or hangul (Cervus elaphus hanglu) outside Dachigam National Park accentuated by habitat suitability assessment. Study results indicate that hangul is restricted to an effective area of 351.15 Km2 outside Dachigam National Park. The overall mean hangul encounter rate outside Dachigam was 0.043 hangul/kilometer walk. The overall hangul sex ratio outside Dachigam was 11.81 males/100 females and the fawn to female ratio was 5.93 fawn/100 females. The overall hangul density outside Dachigam turned out to be 0.49 hangul/Km2 The isolated hangul population outside Dachigam NP and the fragile habitats therein need immediate attention for their effective management and long term conservation. Overa Wildlife Sanctuary and Shikargah Conservation Reserve are considered the alternate potential reintroduction sites for establishing a second viable hangul population outside Dachigam National Park. There is an urgent need for early initiation of the hangul conservation breeding programme for reintroduction/ repopulating existing good habitats in the hangul relic areas, beginning with the Shikargah-Overa ranges in Udder Valley. Development of a scientific based programme for regulated monitoring ofthese relic hangul populations and to identify ideal corridors to help dispersion of Hangul.